Analisis Strategi Menuju Eco Green Kampus Menggunakan Metode SWOT Pada Kampus Universitas Hasyi Asy'ari Jombang - Mohammad Nur Fatta Muzzakki; Titin Sundari; Meriana Wahyu Nugroho; Rahma Ramadhani (Fakultas Teknik Universitas Cenderawasih, 2023)
Civil Engineering is the study of planning, construction, and maintenance of physical structures such as bridges, buildings, and roads. These include sub-fields such as geotechnical, structures, transportation, hydraulics and environmental management. Civil engineers also study ways to manage natural and environmental resources used in construction projects Civil engineering can be used in eco-green environmental analysis. One example is in the planning and construction of green buildings, which are buildings that are designed and constructed in an environmentally friendly way. Civil engineering can be used to analyze and evaluate various aspects of the environment, such as energy efficiency, natural resource use, water management, and greenhouse gas emissions Civil engineering can also be used in the planning and construction of environmentally friendly roads, such as eco-friendly country roads, walking, and bicycle roads.